Analisis Perbandingan Produktivitas Alat Pancang Drop Hammer dan Jack in Pile Proyek Pembangunan SMAN 14 Samarinda - Adde Currie Siregar; Santi Yatnikasari; Fitriyati Agustina; Vebrian Vebrian; Muhammad Jalil (Universitas Kristen Maranatha, 2023)
Along with the development of construction projects, many tools have been created and developed to assist and facilitate activities in construction projects. In carrying out the selection of tools, it is very necessary to plan properly and carefully according to the conditions of the project and the ability of the workers. One tool that is generally used in projects for tall buildings is the piling tool for working on the foundation. In the construction project of SMAN 14 Samarinda, the rigging tools are used, namely drop hammer and jack in pile. This study discusses productivity and several strategies to increase the duration of pile equipment. The data used is obtained from the project in the form of pile tool cycle time data. From the analysis it is known that the average productivity value of the jack in pile is 2.19 and the drop hammer is 1.20. From this productivity, the jack in pile is more efficient than the drop hammer. The use of a drop hammer was chosen because it is relatively inexpensive and the jack in pile was chosen because this method uses static pressure without causing negative impacts (noise and vibration) to the residents around the project. The piling tools used must prioritize the economic value aspects and without negative impact on the community.